The Development of Android Based Instructional Media to Improve Mathematical Understanding on Pythagorean Theorem - Piyo, Sri Herawati M.; Bito, Nursiya; Takaaendengan, Bertu Rianto (IKIP Siliwangi, 2026)
Mathematical understanding is an essential goal of mathematics learning, particularly for abstract topics such as the Pythagorean Theorem, which require strong conceptual comprehension. However, mathematics instruction at the junior high school level is still largely dominated by conventional methods with limited use of interactive learning media, causing students to experience difficulties in understanding concepts. This study aims to develop an interactive Android-based learning multimedia, Pytha-Go, for the Pythagorean Theorem material for eighth-grade students at SMP Negeri 13 Tibawa. This research employed a Research and Development (R&D) approach using a modified 4D development model consisting of three stages: Define, Design, and Develop. The Define stage identified learning problems and student needs through observations and interviews. The Design stage focused on designing the structure, learning content, and interface of the multimedia. The Develop stage involved media production, expert validation, readability testing, and limited trials. Data were collected using media and material expert validation questionnaires, media readability test instruments, teacher observation sheets, and student response questionnaires. The results showed that the average scores from media and material expert validation were 3.23 and 3.17, categorized as very valid and valid. The media readability test obtained an average score of 3.34, indicating that the multimedia is feasible. Teacher observation and student response scores were 3.35 and 3.58, respectively, categorized as very practical. Based on these findings, it can be concluded that the Pytha-Go Android-based learning multimedia is feasible and practical for supporting the learning of the Pythagorean Theorem for eighth-grade students.